Return to competition after an Achilles tendon rupture using both on and off the field load monitoring as guidance: A case report of a top-level soccer player. (January 2018) - Fanchini, Maurizio; Impellizzeri, Franco M.; Silbernagel, Karin Grävare; Combi, Franco; Benazzo, Franco; Bizzini, Mario
Abstract: Objectives: To describe the Return to competition after Achilles Tendon rupture (ATR) in an elite soccer player. Design: Case report. Setting: Return to sport (RTS) of a professional soccer player who suffered an ATR during a match. The RTS phase started 15 weeks after surgery and specific on-field activities were gradually introduced. Criteria used to monitor the transition through the different phases were strength and endurance of the calf muscle and ability to sustain specific on-field training loads (TL) monitored with Global Positioning System and heart-rate system. TLs were weekly compared to pre-injury values to evaluate recovery and to prescribe future sessions. Participant: A 39-year-old (height 178 cm, weight 75 kg) elite soccer defender player, playing in Italian Serie-A league. Results: Days of absence were lower compared to a cohort presented in UEFA study (119 versus 161 ± 65 days, respectively). External-TL and Internal-TL were organized to gradually increase during RTS and resulted in higher values prior to return to competition compared to pre-injury values. Concentric plantar flexion peak torque increased till 9th months after surgery. Conclusions: Monitoring of the field activities allowed comparison with pre-injury values and provided a useful and functional criteria to pass return to team activity and competition.